Chemical and Microbiological Characteristics of Canned Rendang Seasoning (Temperature and Sterilization Time Study) - Syahidah, Fathimah Sarah; Yulistiani, Ratna; Nurhikmat, Asep (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This study aimed to evaluate the effects of sterilization temperature and time on the chemical and microbiological characteristics of canned rendang seasoning. A Completely Randomized Design (CRD) with two factors was employed, using sterilization treatments at 121°C and 126°C for 10 and 15 minutes. Observed parameters included F0 value , moisture content, protein, fat, ash, and the prevalence of Clostridium botulinum. The highest F0 value was recorded at 126°C for 10 minutes (28.70 minutes); however, the treatment of 121°C for 15 minutes (F0 = 5.98 minutes) was selected as optimal, as it meets food safety standards without compromising chemical quality. Microbiological analysis yielded negative results for C. botulinum across all treatments up to day 30 of storage. Chemical characteristics remained relatively stable, with moisture content ranging from 58.55% to 58.94%, ash content from 4.119% to 4.339%, protein content from 28.486% to 28.731%, and fat content from 17.697% to 18.111%, with no significant differences among treatments. Sterilization at 121°C for 15 minutes is recommended as the optimal condition for producing safe and high-quality canned rendang seasoning suitable for both domestic and export markets. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-BeingSDG 12: Responsible Consumption and ProductionSDG 9: Industry, Innovation and Infrastructure